2016
DOI: 10.1177/0011128714542505
|View full text |Cite
|
Sign up to set email alerts
|

Social Bonds, Juvenile Delinquency, and Korean Adolescents

Abstract: Social bonds theory is one of the most influential and tested perspectives for explaining juvenile delinquency, yet tests have often been methodologically limited. Prior research has failed to examine how intra- and interindividual variation in social bonding influences delinquency. In addition, there are few applications of this theory to non-Western contexts. Thus, the current study attempts to test the cross-cultural generalizability of social bonds theory and overcome weaknesses of prior research. We use l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 60 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…As a result, the present study used social bond theory to examine compliance with ISP (see Dong et al, 2021;Hwang & Um, 2021;Ifinedo, 2014Ifinedo, , 2018. Using this theory, Peterson et al (2016) found that attachment to parents (represented in parental supervision) and commitment (represented in a GPA increase) were the main factors in reducing juvenile delinquency. The factors of attachment, commitment, and personal belief are described in the following sections, while involvement is discussed separately under "Involvement Theory.…”
Section: Social Bond Theorymentioning
confidence: 94%
“…As a result, the present study used social bond theory to examine compliance with ISP (see Dong et al, 2021;Hwang & Um, 2021;Ifinedo, 2014Ifinedo, , 2018. Using this theory, Peterson et al (2016) found that attachment to parents (represented in parental supervision) and commitment (represented in a GPA increase) were the main factors in reducing juvenile delinquency. The factors of attachment, commitment, and personal belief are described in the following sections, while involvement is discussed separately under "Involvement Theory.…”
Section: Social Bond Theorymentioning
confidence: 94%
“…Despite Peterson et al's [23] study, little is known about the association between parental attachment and delinquency in traditional societies in general and in Arab society in particular. The few studies that have explored the association between parental attachment and delinquency among Arab adolescents [24,25] found that attachment to parents had a significant impact on reducing delinquent behaviors.…”
Section: Attachmentmentioning
confidence: 97%
“…According to the theory, a breakdown of attachment in the life of the child and/or lower levels of parental involvement may increase the likelihood of children's involvement in delinquency and antisocial behavior [22]. Peterson et al [23] explored the applicability of social bond theory to youth delinquency in South Korea. They found that delinquent behavior among Korean adolescents was found to be more constrained by particular social bonds, such as parental supervision.…”
Section: Attachmentmentioning
confidence: 99%
“…Understanding these two types of problem behaviour requires the use of an integrated framework. The theories of self-control (also known as the general theory of crime), differential association (i.e., association with delinquent peers), and social bond (i.e., meaningful attachment and participation in convention 6 activities), which are among the most influential and empirically tested theoretical perspectives for the explanation of youth risk and delinquent behaviour (McCuddy, 2021;Meldrum et al, 2009;Peterson et al, 2016;Vera & Moon, 2013), are particularly useful. These theories point primarily to the vitality of familial (i.e., parents) and nonfamilial (i.e., peers) relationships in the prohibition or development of problem behaviour.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The basic postulate of the social bond theory is that attachment (i.e., affective ties to significant others such as family members and peers), commitment (i.e., investment in conventional activities such as the pursuit of educational goals), involvement (i.e., time and energy devoted to participation in conventional activities such as school or religious events), and belief (i.e., adherence to societal values and rules) are four vital elements that will prevent individuals from engaging in crime (Hirschi, 1969). There is considerable empirical evidence showing support for the social bond theory in explaining the onset and persistence of criminal pathways (Cernkovich & Giordano, 1992;Chan & Chiu, 2015;Chapple et al, 2005;Cusick et al, 2012;Felson & Staff, 2006;Hart & Mueller, 2013;Peterson et al, 2016;Liu & Kaplan, 1999;Sabatine et al, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%